Leflunomide therapy for IgA vasculitis with nephritis in children - Ling Hou; Zhou Zhang; Yue Du (BMC, 2021)
Abstract Background Henoch-Schönlein purpura (HSP), also called IgA vasculitis, is a systemic vasculitis characterized by deposits of immunoglobulin A in blood vessels. Renal impairment of these patients is the main determinant of prognosis. The optimal treatment of HSP nephritis (HSPN) in children remains controversial, but many clinicians administer an immunosuppressive agent with a corticosteroid. A previous study reported that leflunomide (LEF) with a corticosteroid was effective for adult patients with HSPN and nephrotic proteinuria. However, data on this treatment in pediatric patients is limited. Methods We described our experience at a single center on the use of LEF in 5 pediatric patients who had IgA vasculitis with proteinuria that was nearly 50 mg/kg (nephrotic range) and remained high despite administration of intravenous steroid, and biopsy-proven nephritis. All patients had class II to IIIb lesions based on the International Study of Kidney Disease in Children (ISKDC). Results We successfully treated all 5 children who had IgA vasculitis with nephritis using LEF with a corticosteroid. Four patients achieved a complete remission of proteinuria, and 1 patient had significantly reduced proteinuria. The children received LEF for 6 months to 12 months, and none of them had severe adverse events. Conclusions To our knowledge, this is the first case series to report successful treatment of pediatric HSPN with LEF in combination with a corticosteroid.